Late Bayesian inference in mental transformations - Evan D. Remington (Nature Portfolio, 2018)
Humans compensate for sensory noise by biasing sensory estimates toward prior expectations, as predicted by models of Bayesian inference. Here, the authors show that humans perform ‘late inference’ downstream of sensory processing to mitigate the effects of noisy internal mental computations.